Nickel in Buli Coastal Area, East Halmahera - Hersenanto Catur Widiatmoko; Eddy Mirnanda; Hananto Kurnio (BULLETIN OF THE MARINE GEOLOGY, 2020)
Fragments of ultramafic, metamorphic, basalt and serpentine compose coastal sediments. These fragments derived from outcrops in hinterland as well as the coast. Existence of greywacke sandstone through microscopic observation in coastal sediments indicate deep sea derivation. Marine sediments also show almost the same composition with coastal sediments.Rock fragment abundances of ultramafic (10-47%), serpentine (12-24%) and metamorphic (3-12%) in stream and coastal sediments which have direct relation with the presence of nickel metal in the research area were resulted from petrographic analyses. While mineralographic analyses of heavy mineral concentrate from wooden pan show the existence of ferro nickel (Fe-Ni) and nickeline (Ni-As) in coastal and stream sediments. XRF analyses show nickel contents in seabed sediments 0.0140 to 0.793 %, chromite 0.0179 to 0.1128% and iron 1.2 to 6.85%. Coastal water nickel distribution is controlled by local trapped waves in Buli Bay that excite by equatorial Pacific Ocean waves propagate westward. Nickel occurrences in marine sediments would be an interesting further research.Keywords: nickel, Buli coastal area, East HalmaheraFragmen-fragmen ultramafik, metamorfik, basalt dan serpentin menyusun sedimen pantai. Fragmen-fragmen ini berasal dari singkapan baik di darat maupun di pantai. Dijumpainya fragmen batupasir grewake yang teramati melalui mikroskop dalam sedimen pantai mengindikasikan asal laut dalam. Sedimen dasar laut menunjukkan kecenderungan komposisi yang hampir sama dengan sedimen pantai. Kelimpahan fragmen batuan ultramafik (10-47%), serpentin (12-24%) dan metamofik (3-12%) dalam sedimen sungai dan pantai yang memiliki hubungan langsung dengan keberadaan logam nikel di daerah penelitian dihasilkan dari analisis petrografi. Sedangkan analisis mineralografi pada konsentrat mineral berat hasil dulang mendapatkan fero nikel (Fe-Ni) dan nikelin (Ni-As) dalam sedimen pantai dan sungai.Analisis XRF mendapatkan nikel dalam sedimen dasar laut dengan kandungan 0,0140 hingga 0,793%, kromit 0,0179 hingga 0,1128% dan besi 1,2 hingga 6,85%. Sebaran nikel di perairan pantai dikontrol oleh gelombang lokal yang ditimbulkan oleh gelombang Samudera Pasifik ekuator yang bergerak ke barat. Keterdapatan nikel dalam sedimen dasar laut dapat menjadi riset yang menarik di masa datang.Kata kunci : nikel, pantai Buli, Halmahera Timur.